Regulation and governance matters in the management of social death fund under Malaysian mosques - Syed Ibrahim, Sharifah Norhafiza; Jaaffar, Mohd Yassir; Mustafa, Mohd Ariff; Bani, Hamidah; Syed Alwi, Sharifah Faigah (2023)
To explore regulations and governance matters related to Malaysian mosques in managing the social death fund (khairat). This study employed a qualitative research method. Data was collected via semi-structured interviews with respondents from selected State Islamic Religious Councils (SIRC) and State Mosque Management Departments (SMMD). Respondents were chosen based on a purposive sampling. The transcribed interviews were organized, coded, and analyzed by ATLAS.ti 23. SIRC representatives stated the mosque committees were accountable to at least three parties: SIRCs, SMMDs, and the audit unit. Under the State Islamic Religion Administration Enactment, the council is the sole trustee of all registered mosques and musollas (surau) in Malaysia. Depending on the state, examples of the relevant source of regulations are the Mosque and Surau Regulations 2017, Section 104, Section 96, and Article 43 (1). However, these rules only pertain to the functions, rights, and responsibilities of the mosque committees, collection of general khairat, and management of the cemeteries. The mosque committees that manage the khairat are not subjected to any direct regulations by the Islamic authorities. Instead, the regulations and governance matters are being imposed indirectly via the enactment, rules, and policy issues for the mosques. The most important element in existing practice to govern the management of khairat is trust and obligation to serve the community for the sake of Allah. The officials from the SIRCs prefer the social death fund (khairat) to be managed by the mosque committees rather than by separate entities. The source of regulations discussed in this paper only applies to the selected states only. The research findings provide empirical evidence for the SIRC to craft new policies that cover social death fund (khairat) in the future. The study findings were based on primary data from state Islamic authorities and the mosque committees entrusted to administer social death fund (khairat) in rural areas.